(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Feminism advocates for the equal rights of women—referred to as "The Second Sex"—across all spheres of life, including education, politics, religion, economics, society, culture, and ethics. The roots of feminist thought can be traced back to 14th-century France, where Christine de Pisan (1364–1430), regarded as the first feminist philosopher, boldly challenged societal norms by advocating for female education. Since then, feminism has evolved through various waves, each addressing specific gender-based injustices according to the needs of its time. This paper examines the premise that Islam, when properly understood and implemented, inherently upholds the principles that feminism seeks to achieve, regardless of religious or political identity. It raises the critical question: Is there still a need for feminist movements if Islamic principles concerning women’s rights are genuinely practiced in modern society? The study further explores the root causes of the continued suffering, exploitation, and marginalization of women, identifying the key forces responsible for these injustices. Through a qualitative research approach employing textual, thematic, and content analysis, this research draws upon feminist theories of Jean-Jacques Rousseau (1712), Mary Wollstonecraft (1759), Begum Rokeya (1880), Simone de Beauvoir (1907), and Malala Yousafzai (1997). These feminist perspectives are critically compared and contrasted with Islamic teachings regarding women’s rights to evaluate whether feminism remains a necessary movement in the 21st century. The study concludes by offering potential solutions to bridge the gap between theoretical rights and lived realities, aiming for a just and equitable society for women.